PERENCANAAN KONSTRUKSI SHEET PILE, PADA PERKUATAN TEBING SUNGAI KARANG MUMUS, JALAN, S. PARMAN KOTA SAMARINDA - HARTONO, TRIE (KURVA S JURNAL MAHASISWA, 2020)
Structural calculations on retaining walls are calculated, according to accurate data in the field, laboratory data. with the goal of calculation is to reach a constant value that is at its maximum value because the main factor in handling these landslides is a technical standard and then associated with safety factors. So that the vulnerability of the landslide area, especially in the Karang Mumus River Cliff, Precisely on the Road, S.Parman can be solved by the reinforcement of the river cliffs using sheet piles, it is expected that the settlement using this method can overcome the problem of landslides in other areas not only Tebing Sungai Karang Mumus, Samarinda city only, but in other areas in Indonesia, especially in East Kalimantan. Observation in the field shows that knowledge in college is equipped with knowledge and insight in the field, especially in the field of field management to achieve successful projects.